Occult hepatitis B virus infection: risk for a blood supply, but how about individuals’ health? - Michael X. Fu; Ahmed Elsharkawy; Brendan Healy; Celia Jackson; Daniel Bradshaw; Emma Watkins; Ines Ushiro-Lumb; Jaisi Griffiths; James Neuberger; Kathryn Maguire; Monica Desai; Neil McDougall; et al. (EClinicalMedicine)
Summary: The implementation of effective blood donation screening for hepatitis B virus (HBV) anti-core antibodies with highly sensitive molecular HBV DNA detection in low-endemic countries like the United Kingdom has improved blood safety. However, the linkage to care and management for blood donors with occult HBV infection (OBI) is a complex dilemma involving virological, clinical, methodological, and social issues. Limited evidence suggests that OBI may accelerate the progression of liver disease and cancer. The need for a specialist referral for donors identified with OBI carries mixed opinions from blood establishments, hepatologists, and public health. Following extensive multidisciplinary discussions, experts agree upon a need for clear messaging for donors and to consider the oncogenic implications of OBI. Proposals for future studies are identified, and the applicability of the recommendations in low-resource, high-endemic regions is considered, as well as the inclusion of OBI in global hepatitis elimination targets.